1.75. Rozwiąż nierówności: a) 2 ^ (3x – 2) >= 5 ^ (x – 2/3) c) 13 * 14 ^ (3x) + 2 ^ (3x) * 7 ^ (3x) <= 1 f) (1/9) ^ ((2x - 3)/(x + 2)) < 81 (3/7) ^ ((4x - 3)/(x + 2)) >= root(4, 49/9) 4/3 * (2/3) ^ (x + 2) + 4/9 * (2/3) ^ (x + 1) >= 8/9 d) (0, 4) ^ (x + 3) + (2, 5) ^ (- x – 2) < 3, 5 b) 3 ^ (2x + 2) - 2 * 3 ^ (x + 2) - 27 < 0 d) 16 ^ x + 3 * 2 ^ (2x + 1) + 8 < 0 b) 5 ^ (3x) - 2 * 5 ^ (2x) - 5 ^ (x + 1) - 50 > 0 d) ( 1 2 )^ 3/ +64<( 1 2 )^ x-2 *(1+2^ 2-x ) b) 16^ |x+2| *16^ x-3| <=2^ x+31 d) (1/2) ^ (x + 3) * 8 ^ (2x) > 2 ^ |x – 1| b) 6 ^ x – 3 * 5 ^ x < 10 ^ x - 3 ^ (x + 1) d) 10 ^ x - 4 * 5 ^ x < 125 * 2 ^ x - 500 f) 6 ^ x + 3 * 7 ^ x < 21 ^ x + 3 * 2 ^ x (x/5) = b) 7 ^ (x - 3) < 3 ^ (2x - 6) d) 6 ^ (2x + 4) - 3 ^ (3x) * 2 ^ (x + 8) > 0

1.75. Rozwiąż nierówności: a) 2 ^ (3x – 2) >= 5 ^ (x – 2/3) c) 13 * 14 ^ (3x) + 2 ^ (3x) * 7 ^ (3x) <= 1 f) (1/9) ^ ((2x – 3)/(x + 2)) < 81 (3/7) ^ ((4x – 3)/(x + 2)) >= root(4, 49/9) 4/3 * (2/3) ^ (x + 2) + 4/9 * (2/3) ^ (x + 1) >= 8/9 d) (0, 4) ^ (x + 3) + (2, 5) ^ (- x – 2) < 3, 5 b) 3 ^ (2x + 2) – 2 * 3 ^ (x + 2) – 27 < 0 d) 16 ^ x + 3 * 2 ^ (2x + 1) + 8 < 0 b) 5 ^ (3x) – 2 * 5 ^ (2x) – 5 ^ (x + 1) – 50 > 0 d) ( 1 2 )^ 3/ +64<( 1 2 )^ x-2 *(1+2^ 2-x ) b) 16^ |x+2| *16^ x-3| <=2^ x+31 d) (1/2) ^ (x + 3) * 8 ^ (2x) > 2 ^ |x – 1| b) 6 ^ x – 3 * 5 ^ x < 10 ^ x – 3 ^ (x + 1) d) 10 ^ x – 4 * 5 ^ x < 125 * 2 ^ x – 500 f) 6 ^ x + 3 * 7 ^ x < 21 ^ x + 3 * 2 ^ x (x/5) = b) 7 ^ (x – 3) < 3 ^ (2x – 6) d) 6 ^ (2x + 4) – 3 ^ (3x) * 2 ^ (x + 8) > 0

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz